Specific agglutination of tanned red cells coated with a globulin fraction of an antithyroid serum by saline extracts of thyroid glands. Issue 6 (November 1965) - MacLeod, Ian
Abstract : Experiments are described in which tanned red cells coated with a globulin fraction of human serum with a high titre of antibody to human thyroglobulin were agglutinated by saline extracts of human thyroid gland and thyroglobulin but not by other tissue extracts. It is suggested that the linkage is due to a specific antigen antibody reaction between cell-bound antithyroid antibody and thyroglobulin in solution.